IMPROVING CIVIL STUDY LEARNING RESULTS WITH THE COOPERATIVE LEARNING MODEL TYPE: GROUP INVESTIGATION (GI) IN MAIN MATERIALS OF VIOLATION OF HUMAN RIGHTS IN PANCASILA PErSPECTIVE IN CLASS XI, SMA NEGERI 2 AMARASI 2018 - Oni Simons Rafael (Warta Pendidikan | e-Journal, 2021)
The purpose of this Classroom Action Research is an effort to improve student learning outcomes in Civics learning on the Main Material "Cases of Human Rights Violations" in Class XI Language Semester 1 students of SMA Negeri 2 Amarasi in the 2018/2019 Academic Year. The research method is Classroom Action Research with a participatory-collaborative approach between researchers and teachers and students. As the subject and object of research (Moleong, 2013: 181) are students of class XI Language SMA Negeri 2 Amarasi Semester 1 in the 2018/2019 academic year, totaling 31 people. The research object is; (1). application of the Type GI Cooperative Learning Model; and (2). Learning outcomes. The results of the study show that the use of the Group Investigation (GI) learning model improves student learning outcomes in the PKN learning process with the main material "Cases of Human Rights Violations" in Class XI Language Semester 1 SMA Negeri 2 Amarasi Academic Year 2018/2019, namely completeness of student learning from 29.03% increased to 54.83% in cycle I and increased to 100% in cycle II. Meanwhile, 75% teacher performance in pre-cycle increased 80% in cycle I and increased to 100% in cycle II